Directing the documentary - Rabiger, Michael; Hermann, Courtney (Routledge, 2020)
"Directing the Documentary is the definitive book on the documentary form, that will allow you to master the craft of documentary filmmaking. Focusing on the hands-on work needed to make your concept a reality. It covers the documentary filmmaking process from top to bottom, providing in-depth lessons on every aspect of preproduction, production, and postproduction. The book includes dozens of projects, practical exercises, and thought-provoking questions, and offers best practices for researching and honing your documentary idea, developing a crew, guiding your team, and much more. This fully revised and updated 7th edition also includes brand new content on the rise of the documentary series, the impact of video on demand and content aggregators, updated information on prosumer and professional video (including 4K+), coverage of new audio & lighting solutions and trends in post-production, coverage of the immersive documentary, and provides practical sets of solutions for low, medium, and high budget documentary film productions throughout. The companion website has also been fully updated to include interviews with current documentary filmmakers, additional project ideas, and student film examples. By combining expert advice on the storytelling process, the technical aspects of filmmaking and commentary on the philosophical underpinnings of the art, this book provides the practical and holistic understanding you need to become a highly-regarded, original, and ethical contributor to the genre. Ideal for both aspiring and established documentary filmmakers, this book has it all"-- |c Provided by publisher.